Based Purchasing Decisions Product Quality, Prices and Promotions - Dwi Gemina; Samsuri; Dinda Ivana Rismawati (International Journal of Integrated Science and Technology, 2024)
In facing an increasingly strong and tight competitive environment, every company is required to be able to optimize its economic resources in order to increase the competitiveness of its products in the market, and to be able to carry out a series of effective marketing strategies and always develop these marketing strategies continuously and sustainably. This research aims to determine and analyze the influence of product quality, price and promotion on purchasing decisions for Hori LED lights in the city of Bogor. This research design uses descriptive and verification methods. The sampling technique in this research uses probability sampling with a simple random sampling technique. The number of respondents was 100 people. The subjects of this research are all consumers who have purchased Hori Lamp products in Bogor City, and the objects of this research are product quality, price, promotions and purchasing decisions. The tools used in this analysis are path analysis, multiple correlation analysis, coefficient of determination analysis and hypothesis testing with the F test and t test. The research results show that product quality has a direct and positive influence on purchasing decisions for Hori LED lights in Bogor City. Price has a direct and positive influence on purchasing decisions for Hori LED lights in Bogor City. Promotions have a direct and positive effect on purchasing decisions for Hori LED lights in Bogor City. Product quality has a positive relationship with price. Price has a positive relationship with promotion. Product quality has a positive relationship with promotion.